Improvement in the Estimation of Inhaled Concentrations of Carbon Dioxide, Nitrogen Dioxide, and Nitric Oxide Using Physiological Responses and Power Spectral Density from an Astrapi Spectrum Analyzer - Shisir Ruwali; Jerrold Prothero; Tanay Bhatt; Shawhin Talebi; Ashen Fernando; Lakitha Wijeratne; John Waczak; Prabuddha M. H. Dewage; Tatiana Lary; Matthew Lary; Adam Aker; David Lary (Air, 2025)
The air we breathe contains contaminants such as particulate matter (PM), carbon dioxide (<semantics>CO2</semantics>), nitrogen dioxide (<semantics>NO2</semantics>), and nitric oxide (NO), which, when inhaled, bring about several changes in the autonomous responses of our body. Our previous work showed that we can use the human body as a sensor by making use of autonomous responses (or biometrics), such as changes in electrical activity in the brain, measured via electroencephalogram (EEG) and physiological changes, including skin temperature, galvanic skin response (GSR), and blood oxygen saturation (<semantics>SpO2</semantics>). These biometrics can be used to estimate pollutants, in particularly <semantics>PM1</semantics> and <semantics>CO2</semantics>, with high degree of accuracy using machine learning. Our previous work made use of the Welch method (WM) to obtain a power spectral density (PSD) from the time series of EEG data. In this study, we introduce a novel approach for obtaining a PSD from the EEG time series, developed by Astrapi, called the Astrapi Spectrum Analyzer (ASA). The physiological responses of a participant cycling outdoors were measured using a biometric suite, and ambient <semantics>CO2</semantics>, <semantics>NO2</semantics>, and NO were measured simultaneously. We combined physiological responses with the PSD from the EEG time series using both the WM and the ASA to estimate the inhaled concentrations of <semantics>CO2</semantics>, <semantics>NO2</semantics>, and NO. This work shows that the PSD obtained from the ASA, when combined with other physiological responses, provides much better results (RMSE = 9.28 ppm in an independent test set) in estimating inhaled <semantics>CO2</semantics> compared to making use of the same physiological responses and the PSD obtained by the WM (RMSE = 17.55 ppm in an independent test set). Small improvements were also seen in the estimation of <semantics>NO2</semantics> and NO when using physiological responses and the PSD from the ASA, which can be further confirmed with a large number of dataset.